Beyond Positivism: Reconstructing Kuntowijoyo’s Prophetic Social Science in Contemporary Islamic Social Theory - Arhan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Modern social science, shaped by a positivist epistemology, tends to separate facts from values, so religion is often placed outside the realm of legitimate social knowledge, even though in many Muslim societies it continues to shape norms, authority, and public life. This study aims to reconstruct Kuntowijoyo’s Prophetic Social Science as a conceptual-analytical framework within contemporary Islamic social theory. This research is a conceptual paper employing a qualitative literature review approach. The data were collected purposively from Kuntowijoyo’s major works, especially Islam Sebagai Ilmu and related writings, as well as supporting literature in social theory, Islamic epistemology, and recent studies on religion, normativity, and knowledge production. The analysis was conducted through reflexive thematic analysis by means of repeated close reading, identification of conceptual patterns, thematic grouping, and interpretive reconstruction of theoretical relationships. The findings show that Prophetic Social Science can be reconstructed not merely as a normative-ethical project, but as a conceptual-analytical framework that integrates revelation, reason, and social reality in a dialogical manner. The categories of humanization, liberation, and transcendence can therefore be positioned as analytical tools for examining socio-religious dynamics such as authority, inequality, moral contestation, and institutional relations. This study implies that Prophetic Social Science offers an alternative path for developing a non-reductionist social theory that connects normative orientation with empirical analysis. Ilmu sosial modern yang dibentuk oleh epistemologi positivistik cenderung memisahkan fakta dari nilai sehingga agama kerap ditempatkan di luar sumber pengetahuan sosial yang sah, padahal dalam banyak masyarakat Muslim, agama tetap aktif membentuk norma, otoritas, dan kehidupan publik. Penelitian ini bertujuan merekonstruksi Ilmu Sosial Profetik Kuntowijoyo sebagai kerangka konseptual-analitis dalam teori sosial Islam kontemporer. Penelitian ini merupakan artikel konseptual yang menggunakan pendekatan kualitatif berbasis studi literatur. Data dikumpulkan secara purposif dari karya utama Kuntowijoyo, khususnya “Islam Sebagai Ilmu” dan tulisan terkait lainnya, serta literatur pendukung dalam teori sosial, epistemologi Islam, dan kajian mutakhir tentang agama, normativitas, dan produksi pengetahuan. Analisis dilakukan melalui reflexive thematic analysis dengan pembacaan berulang, identifikasi pola konseptual, pengelompokan tema, dan rekonstruksi interpretatif atas hubungan teoretis antarkonsep. Hasil penelitian menunjukkan bahwa Ilmu Sosial Profetik dapat direkonstruksi bukan sekadar sebagai proyek normatif-etis, tetapi sebagai kerangka konseptual-analitis yang mengintegrasikan wahyu, rasio, dan realitas sosial secara dialogis. Kategori humanisasi, liberasi, dan transendensi terbukti dapat diposisikan sebagai perangkat analitis untuk membaca dinamika sosio-keagamaan seperti otoritas, ketimpangan, kontestasi moral, dan relasi institusional. Implikasi penelitian ini adalah bahwa Ilmu Sosial Profetik menawarkan jalur alternatif bagi pengembangan teori sosial non-reduksionis yang menghubungkan orientasi normatif dengan analisis empiris.